Support Systems, Strategies, and Self-Efficacy of Preschool Teachers in Handling Separation Anxiety - Jucoy, Ronah Faith (JPAIR Institutional Research, 2022)
The study aimed to ascertain the support system, strategies, and self-efficacy of preschool teachers in handling learners’ separation anxiety. It also determined the significant relationship between the support system and preschool teachers’ self-efficacy. It also determined if there is a significant relationship between the strategies and the preschool teachers’ self-efficacy. Descriptive and correlational method was used in the study. Moreover, the quantitative results were supported by a qualitative interview with the preschool teachers. The respondents of the study were the 127 preschool teachers in Sarangani Division. The instrument used was a researcher-made questionnaire validated by the experts and was pilot tested. The results showed that the teachers’ support system was a moderate extent. Also, they have used overprotection, avoidance reinforcement, encouragement, and rewards to handle learners’ separation anxiety to a great extent. Additionally, their self-efficacy is to a high extent. Lastly, the teachers shared the following success stories: enjoying the company of the learners, being a resourceful preschool teacher, showing love and compassion towards the learners, collaborating with the learners, and extending their Patience for the learners. Based on the results, the researcher developed an intervention program dubbed PROJECT SEPAX.